2015
DOI: 10.1556/oh.2015.30121
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among Hungarian physicians. Who are the most jeopardized?

Abstract: Bevezetés: A kiégés a XXI. század orvoslásának egyik legnagyobb kihívást jelentő kérdése. Célkitűzés: A szerzők célul tűzték ki a magyarországi orvosok (n = 4784) kiégésmutatóinak felmérését, valamint e mutatók és a munkavégzés körülményeit érintő legmeghatározóbb aspektusok (munkaórák, ügyeleti munkavégzés, több munkahelyen való helytállás) összefüggéseinek elemzését. Módszer: Orvosok körében végzett országos, reprezentatív, online kvantitatív felmérés eredményeinek deskriptív elemzése. Eredmények: A vizsgála… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 31 publications
1
3
1
Order By: Relevance
“…As the data of the study was collected through Facebook, this might have caused this discrepancy, and it should be taken into consideration. The results of our research coincided with the results of the majority of research by foreign authors; greater burnout was noticed among the employees younger than 40 years old (23,(28)(29)(30)(31)(32)(33)(34). However, the results of one research show that burnout becomes more severe as the age increases (24).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As the data of the study was collected through Facebook, this might have caused this discrepancy, and it should be taken into consideration. The results of our research coincided with the results of the majority of research by foreign authors; greater burnout was noticed among the employees younger than 40 years old (23,(28)(29)(30)(31)(32)(33)(34). However, the results of one research show that burnout becomes more severe as the age increases (24).…”
Section: Discussionsupporting
confidence: 90%
“…Our research did not notice a statistically significant link between the healthcare chain (outpatient or inpatient) and burnout, although the results of foreign researchers show that specialists working in the inpatient care chain tend to suffer from a more severe burnout and have the lowest resilience score (29)(30). Such differences could be caused by dissimilarities in the existing job specifics for inpatient and outpatient care chains in different countries, where the job in the inpatient care chain is more stressogenic.…”
Section: Discussioncontrasting
confidence: 81%
“…The integrated model of Carlson et al [ 22 ] identified different types of work-life conflict: time-based (arising from lack of time), stress-based (arising from role-mismatch stress), and behavioural-based (arising from different behavioural expectations). These studies showed that difficulties arising from the need to coordinate work and family life have an impact on job satisfaction [ 23 ], and physical and mental health [ 24 , 25 ] Several studies add that WLB impacts vital exhaustion, depression, and burnout [ 26 28 ]. There is a significant negative correlation between WLB and the emotional exhaustion (EE) and the depersonalisation (DP) subscale of burnout [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have emphasized the importance of recognizing physician satisfaction as a relevant problem for healthcare service delivery. Dissatisfaction of physicians highly affects them as it has been linked with burnout [3], self-reported psychiatric symptoms, poorer perceived mental health [4,5], and intention to leave the practice [6]. There is also evidence that the level of physician satisfaction may influence the quality of healthcare services [5,7,8].…”
Section: Introductionmentioning
confidence: 99%